2012
DOI: 10.1051/0004-6361/201219616
|View full text |Cite
|
Sign up to set email alerts
|

Upper limit for the D2H+ortho-to-para ratio in the prestellar core 16293E (CHESS)

Abstract: The H + 3 ion plays a key role in the chemistry of dense interstellar gas clouds where stars and planets are forming. The low temperatures and high extinctions of such clouds make direct observations of H + ratio as well as the para-D 2 H + /ortho-H 2 D + ratio from a non-local thermodynamic equilibrium analysis. The comparison between our chemical modeling and the observations suggests that the CO depletion must be high (larger than 100), with a density between 5 × 10 5 and 10 6 cm −3 . Also the upper limit o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 45 publications
4
17
0
Order By: Relevance
“…3). Finally we note that the ortho/para ratios predicted by our models at t = 10 6 years are for the most part compatible with recent modeling results of Vastel et al (2012; their complete depletion case), although our chemical network is much larger and the present model includes a time-dependent treatment of depletion.…”
Section: Ortho/para Ratiossupporting
confidence: 89%
“…3). Finally we note that the ortho/para ratios predicted by our models at t = 10 6 years are for the most part compatible with recent modeling results of Vastel et al (2012; their complete depletion case), although our chemical network is much larger and the present model includes a time-dependent treatment of depletion.…”
Section: Ortho/para Ratiossupporting
confidence: 89%
“…Assuming a line-of-sight source size of 9.5 or 1140 au, equal to the geometric mean of the FWHM sizes in the plane of the sky, we derive an H 2 volume density of (1.1 − 1.9) × 10 7 cm −3 , depending on the dust temperature. This is an order of magnitude higher than the values derived in earlier single-dish studies (Stark et al 2004;Vastel et al 2012), but consistent with the best-model value of 1.4 × 10 7 cm −2 in the recent study of Bacmann et al (2016). The high central density in the model of Bacmann et al (2016) is in fact directly related to the presence of a temperature gradient.…”
Section: Properties Of the Dust Continuum Sourcesupporting
confidence: 88%
“…This is reminiscent of the velocity differences seen in this source, where the velocity of the emission from deuteriumbearing species Stark et al 2004) are at the cloud velocity of 3.8−4 km s −1 (see the discussion in Vastel et al (2012), where more details on these various points can be found). The line widths found by fitting the HRS spectra are 0.4±0.02 km s −1 for both ND and NH, consistent with line widths measured in this source in other hydrides like ND 2 H .…”
Section: Resultsmentioning
confidence: 70%